Analisis Manfaat dan Dampak Ekonomi Atas Kerja Sama Pemanfaatan (KSP) Pulau Liwungan: Barang Milik Daerah pada Pemerintah Kabupaten Pandeglang - Subagyo, Petrus Teguh (Melati Institute, 2024)
Collaboration in the utilization of Pandeglang Regency Government assets (Liwungan Island) has an impact on regional revenues as well as economic impacts and benefits. This collaboration produces regional income in the form of fixed contribution payments and profit sharing. The amount of investment in the utilization collaboration is IDR 38,400,000,000.00, while the projected operational costs over a 25-year utilization period are IDR 227,915,000,000.00. Economic benefit analysis uses quantitative descriptive methods taking into account a social discount rate of 9% produces a projected economic benefit of IDR 100,120,929,000.00. Analysis of the economic impact using an input-output table, with an injection/stimulus amount of IDR 266,315,000,000.00, the amount of change in value is IDR 360,128,000,000.00 which produces a multiplier of 1,352 times.